Handwritten Alphabet Recognition Using Hamming Network - Arnold Aribowo; Samuel Lukas; Handy Handy (Seminar Nasional Aplikasi Teknologi Informasi (SNATI), 2007)
Handwritten Alphabet Recognition is one of the artificial intelligence applications which provides animportant fundamental for various advanced applications, including information retrieval and human-computerinteraction applications. This paper elaborates a research which is performed to build a system which is able torecognize handwritten latin alphabets in the form of images. The system is developed using the HammingNetwork method.From the experiments of 100 prototypes of data, the system is able to identify handwritten latin alphabetswith 76.97% average accuracy. Mistaken recognitions are mainly caused by the similarity of the alphabetpatterns, such as the pattern of I, T and Z, or the pattern of C and G. The value of ε and the matrix b which aregiven in the system may affect the recognition results.Keywords: Handwritten Alphabet Recognition, Hamming Network